انتقال الولاية في الزواج بسبب عضل الولي وتطبيقاته في جنوب تايلاند: دراسة فقهية تحليلية - دوله، فوزان عثمان (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
The study aims to investigate the definition of a guardian, the legislation and the law that are pertinent to the guardian. The study also explores the replacement of the guardian (Wali) in Islamic marriage due to the resistance of the guardian in the southern provinces of Thailand, causes of the replacement, the practice of the replacement, and the solutions to the replacement. This documentary study focuses on investigating the definition and the general concept of the guardian and the resistance of the guardian. Thus, data were collected from books, studies, and relevant academic articles. The data regarding the practice and the solutions to the resistance of the guardian were also collected from provincial Islamic committees in the southern part of Thailand.